Essential oil composition of Pterospartum tridentatum grown in Portugal - Grosso, A. Clara (2015)
The essential oils, isolated by hydrodistillation and distillation-extraction, from the aerial parts of different populations of Pterospartum tridentatum collected during the flowering phase, at different locations in Portugal, were analysed by GC and GC-MS. All the P. tridentatum populations studied afforded a yellowish oil in a yield 0.05% (v/w). cis-Theaspirane (2-14%), trans-theaspirane (2-17%) and octen-3-ol (2-37%) were, in variable amounts, the dominant components of the oils. Cluster analysis of the essential oil compositions from the nine populations studied, confirmed a major chemical variability. (c) 2006 Elsevier Ltd. All rights reserved.